1990
DOI: 10.1029/wr026i011p02733
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of Single‐Parameter Precipitation Distributions

Abstract: A general procedure was developed for calibrating multiparameter probability distributions of daily precipitation to single-parameter distributions. The approach uses monthly precipitation summaries and data from U.S. Weather Bureau Technical Paper 57 (Miller and Frederick, 1966). The threeparameter beta-P model of daily precipitation amount was calibrated for 33 sites east of the Rocky Mountains. The resulting single-parameter Weibull distribution and two other single-parameter precipitation distributions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
3
32
1
Order By: Relevance
“…Selker and Haith (1990) showed that for 33 United States climate stations east of the Rocky Mountains, the Weibull distribution is superior to other distributions. For wet days the precipitation amount is generated by…”
Section: Amount Of Daily Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Selker and Haith (1990) showed that for 33 United States climate stations east of the Rocky Mountains, the Weibull distribution is superior to other distributions. For wet days the precipitation amount is generated by…”
Section: Amount Of Daily Precipitationmentioning
confidence: 99%
“…ClimGen has the capability to automate the task of parameterizing the historical weather data. Also, while their fi ndings may be location specifi c, Selker and Haith (1990) concluded that the use of a Weibull distribution to represent daily precipitation amounts, as is in Climgen, is superior to other probability distribution functions. The ClimGen developers claim the spline approach is an improvement over the one-term Fourier series used by many other weather generators to model seasonal variations in climate data.…”
Section: Selection Of Climate Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…(6). The inverse CDF of Weibull distribution is based on the single-parameter Weibull distribution estimated by Selker and Haith (1990).…”
Section: Rainfall Amountmentioning
confidence: 99%
“…If it is a wet day, the rainfall amount is generated based on a single-parameter Weibull distribution (Selker and Haith 1990) .…”
Section: P W W If Previous Day Is Wet Daymentioning
confidence: 99%